p63RhoGEF and GEFT are Rho-specific guanine nucleotide exchange factors encoded by the same gene - Lutz, Susanne; Freichel-Blomquist, Andrea; Rümenapp, Ulrich; Schmidt, Martina; Jakobs, Karl-Heinz; Wieland, Thomas (Naunyn-Schmiedeberg's archives of pharmacology, 2004)
Activation of Rho GTPases, which play pivotal roles in diverse cellular functions, is catalysed by specific guanine nucleotide exchange factors (GEFs). We and others (Souchet et al. (2002)) independently cloned a human cDNA encoding a 580 aa protein (p63RhoGEF), which contains a tandem of Dbl homology and pleckstrin homology domains typical for RhoGEFs. In accordance with Souchet et al., recombinant p63RhoGEF interacted with and catalysed GDP/GTP exchange at RhoA, but not Rac1 or Cdc42. Recently, an N-terminally truncated form of p63RhoGEF, termed GEFT, was described as a Rac/Cdc42-specific GEF (Guo et al. 2003). As judged by RT-PCR with specific primers, we were able to detect mRNA variants encoding p63RhoGEF and GEFT within several tissues and cell lines. Apparently, they co-exist within one cell and are derived from the same gene. When expressed in human embryonic kidney cells, both p63RhoGEF and GEFT caused activation of RhoA, but not Rac1 or Cdc42, and induced serum response factor-mediated gene transcription, which was fully blunted by the Rho-inactivating C3 transferase. In line with these data, expression of either p63RhoGEF or GEFT in J82 human bladder carcinoma cells induced the formation of actin stress fibres. We therefore conclude that p63RhoGEF and GEFT are apparently isoforms derived from the same gene and that GEFT, similar to p63RhoGEF, activates RhoA in several cell types.
Gesehen am 04.04.2022